PENGARUH PENANAMAN MODAL DALAM NEGERI (PMDN) DAN PENANAMAN MODAL ASING (PMA) TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) SUMATERA UTARA TAHUN 2000-2018 - Dede Ruslan; Pebri Hastuti; Dedi Irawan (Niagawan, 2020)
This research is titled foreign investment (PMA) and domestic investment (PMDN) on gross regional domestic product (GRDP) in North Sumatra. The purpose of this study was to analyze the effect of PMA and PMDN on GRDP. The method used in this research is a quantitative method that uses mathematical models to present facts or describe statistics to show the relationship between variables namely capital development and domestic investment of regional domestic products in North Sumatra. The results of data processing showed that PMA and PMDN variables in districts / cities in North Sumatra did not have a positive and significant effect on GRDP variables. Meanwhile, procedurally, PMA variable does not have a significant effect on GRDP while PMDN has a positive and significant effect on GRDP. Kata Kunci : Foreign Capital, Domestic Capital, Transition